Estimation of risk measures in energy portfolios using modern copula techniques - Jäschke, Stefan (Technische Universität Dortmund, 2012)
The present paper analyses the dependence structure between WTI and Brent crude oil spot log-returns using modern copula techniques. In a first step we apply several single equation models to the marginals to account for autocorrelation and volatility clustering. Second, to select both copulas and tail copulas characterising the joint dynamics between the time series we implement and evaluate newly introduced bootstrap-based goodness-of-fit tests. Based on each approach, a comprehensive backtesting is performed by simulating and comparing the risk measures Value-at-Risk and Expected Shortfall with historical values.
Discussion Paper / SFB 823;43/2012
Keywords: backtesting; crude oil; goodness-of-fit tests; joint dynamics; risk measures; tail copulas; 310; 330; 620